Disease ecology of rabies in the Great Plains: synthesizing the effects of viral properties, host attributes, and landscape on disease emergence - Barton, Heather D. (Kansas State University, 2010)
Emerging infectious diseases play an increasingly critical role in many biological fields, including conservation biology and public health. Many emerging diseases originate in wildlife, most are caused by viruses, and often emergence is due to adaptation to and amplification in a new host, frequently in areas where ecological transformation is occurring. These emergence patterns suggest that the complex interactions among host, virus, and landscape drive disease emergence. Terrestrial rabies in striped skunks (Mephitis mephitis) in the central Great Plains is an excellent model system to investigate the interactions among the components of disease emergence: host ecology, pathogen properties, and landscape features. Striped skunks are not only numerous in the central Great Plains, they are also the reservoir for two genetically distinct rabies strains that co-occur in the region. Additionally, the landscape in the central Great Plains has undergone significant land use change over the last 70 years through increased urbanization and industrial agriculture practices. I used a combination of molecular and spatial techniques to investigate the interactions among host, pathogen, and landscape. Molecular epidemiology results indicated that rabies strains in the central Great Plains exhibit different epidemiological properties, while population genetic analyses indicated that striped skunks in the region are highly admixed and comprise a single population. Spatial analysis revealed that landscape features such as rivers are not a barrier to striped skunk dispersal, but differentially influence the movement of the two rabies strains. Because striped skunks are reservoirs for many diseases other than rabies and are ubiquitous throughout North America, I also examined the historical movements and distribution of striped skunks in North America using a phylogeographic approach. Results revealed that a combination of multiple Pleistocene dispersal events and Holocene admixture are responsible for the contemporary population structure of striped skunks in North America, and allowed me to place my regional-scale striped skunk rabies study into a larger biogeographic context. My results support the use of a holistic approach for studying emerging infectious diseases that includes studies of viral characteristics, host ecology and biogeography, and spatial features.
Keywords: Rabies; Striped skunk; Disease ecology; Biology, General (0306)